NILAI AKIDAH DALAM GURINDAM DUA BELAS KARYA RAJA ALI HAJI - Azmi, Ulul; Zainal, Rusli (Jurnal Ilmu Budaya, 2016)
Gurindam Dua Belas which was written by Raja Ali Haji has meaningful religious values. In its verses, this work advices its reader. It strengthens that someone who doesn’t apply his/her God’s commands is considered as someone who has no religion. The verses also advise the reader to know his/her religion, Allah, oneself, the world which deceives humans, and to know the life in the after world.